STUDENTS’ PERSPECTIVE TOWARDS ASYNCHRONOUS AND SYNCHRONOUS TEACHING AND LEARNING PROCESS IN A TOEIC PREPARATION CLASS - Dianita; Levita Dwinaya (Jurnal Sastra - Studi Ilmiah Sastra, 2020)
The globally spread Covid-19 pandemic has instantly changed the teaching and learning process. This study captures students’ perspective towards asynchronous and synchronous teaching and learning process in a TOEIC preparation program. The data gathered for the study were collected through a questionnaire consisting of eight open ended questions, which were given to students of a higher educational vocational institution in Bandung previously taking a one month TOEIC preparation program. The result indicates that students involved in this study prefer asynchronous elearning over synchronous because of the lack of infrastructure supports such as stable internet connection and big internet quota. However, generally students have positive perspective towards the use of both asynchronous and synchronous e-learning as those types of e-learning are proved to have good impact on their learning.